Evaluating Success of E-Learning in Different Faculties of a University - Mohammad Javad Shayegan; Amir Ashoori (International Journal of Web Research)
The success of e-learning is still a challenging issue. This study presents a model for the evaluation of the success of e-learning in three different faculties. More specifically, the present article answers the question of whether e-learning success variables are different in different faculties. The method of this study was descriptive-survey research. Evaluating research validity was conducted through confirmatory factor analysis, and Cronbach's alpha was used to measure the reliability of the research instrument. The method of the structural equation was used for modeling. The findings reveal that the students’ opinions in the three faculties about the success variables were significantly different. In the Faculty of Engineering, teaching with a coefficient of 0.93, in the Humanities, service quality with a coefficient of 0.9, and in the Arts Faculty, support quality with a coefficient of 0.82 were identified as the highest impact factors. On the other hand, significant commonalities were observed.